The nature and extent of non-suicidal self-injury in a non-clinical sample of young adults - Hasking, Penelope; Momeni, R.; Swannell, S.; Chia, S. (Routledge, 2008)
This study aimed to examine the nature, extent and correlates of non-suicidal self injury (NSSI) in a non-clinical sample of young adults. Two hundred and eleven participants (18-30 years) completed self-report questionnaires assessing history of NSSI, emotional regulation, coping strategies, symptoms of psychopathology, and alcohol use. Of the sample, 43.6% reported engaging in NSSI; approximately 10% engaged in moderate/severe NSSI. Those that reported NSSI reported greater psychopathology, avoidant coping and alcohol use than those who did not self-injure. The extent of these differences was magnified as the severity of NSSI increased. These findings highlight the need to consider any form of NSSI, no matter how mild, as an indication of distress and ineffective coping.